معوقات تطبيق الجودة في التعليم الابتدائي - طيبي، سارة, مسغوني، لطيفة (جامعة الوادي university of Eloued, 2020)
الملخص: هدفت هذه الدراسة إلى استكشاف معوّقات تطبيق الجودة في التعليم الابتدائي من وجهة نظر معلمي ومفتشي التعليم بالمرحلة الابتدائية بمدينة الوادي. وقد اتبعت الدراسة المنهج الوصفي الاستكشافي، وتمثلت أداة الدراسة في استبيان يتضمن سؤالا مفتوحا لتقصي الظاهرة، وتكوّنت العينة من(100) معلم ومعلمة، و(30) مفتشا لمرحلة الابتدائي تم اختيارهم بطريقة عشوائية عرضية، أمّا الأسلوب الإحصائي فقد اقتصر على النسب المئوية، ثم عرض وتفسير النتائج. وقد توصلت الدراسة إلى وجود معوّقات تحول دون تحقيق الجودة في التعليم الابتدائي تتعلق بالمنهج، والمعلم، والمتعلّم، والإدارة المدرسية. وقد أوصت الدراسة بضرورة معالجة هذه المعوّقات من خلال إعادة النظر في الإصلاحات التربوية الأخيرة قصد النهوض بالمدرسة الجزائرية، وتحقيق الجودة في مسارها التعليمي. Résumé :فرنسية أو انجلزية The purpose of this study is to explore the obstacles to implementing quality in the primary education from the viewpoint of teachers and inspectors in the elementary school in the city Eloued. The descriptive method has been adopted in an exploratory manner, according to the nature of the considered phenomenon. The study has been performed using a questionnaire based on a sample of one hundred(100) primary education male and female teachers and thirty(30) inspectors who were chosen in random. As for the statistical method, it has been applied through percentages(percentage frequency equation); then presentation and interpretation of results there to . The study unveiled some obstacles to achieving quality in the primary education, due to the curriculum, teachers, learners, and school administration . In conclusion, the study recommends removing these hindrances by reviewing the recent educational reforms in order to improve the Algerian school and achieve .quality in its educational performances.
دراسة استكذافية من وجهة نعر معمسي ومفتذي التعميم الابتتاايي بسايشة الهادي
مذكرة ماستر في علوم التربية تخصص إرشاد وتوجيه
Keywords: الجودة في التعليم; Qualité de l'éducation; Quality in education